1999
DOI: 10.1001/archotol.125.12.1305
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Produces Sustained Remissions in Patients With Oral Leukoplakia<subtitle>Results of a Multicenter Prospective Trial</subtitle>

Abstract: The activity of beta-carotene in patients with oral leukoplakia was confirmed. The responses produced were durable for 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 30 publications
0
40
2
2
Order By: Relevance
“…The main reason for the high drop-out rate is thought to be related to the information provided at the time of entry to the trial, that the supplement may increase the risk of lung cancer. The overall response rate of 17.4% (95%, CI 1.9-32.9%) in this study is lower compared with the outcomes reported in previous studies (Table 4) [22][23][24][27][28][29] . This might be related to the lower dose of beta-carotene used here.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The main reason for the high drop-out rate is thought to be related to the information provided at the time of entry to the trial, that the supplement may increase the risk of lung cancer. The overall response rate of 17.4% (95%, CI 1.9-32.9%) in this study is lower compared with the outcomes reported in previous studies (Table 4) [22][23][24][27][28][29] . This might be related to the lower dose of beta-carotene used here.…”
Section: Discussioncontrasting
confidence: 88%
“…It appears that the reported outcomes are not necessarily related to the dosage of supplements used, lengths of trials, or due to a combination of antioxidants. There were five RCTs on oral leukoplakia using betacarotene with or without additional chemopreventive agents, [22][23][24]27,29 and these achieved nearly 50% of overall response rate by the variety of trial designs. However, the timing of assessment for the clinical response was not discussed clearly and none of the studies followed up beyond 15 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…conservative treatment: Can be done by [26,27]. Recurrences were seen after treating the patients conservatively.…”
Section: Treatmentmentioning
confidence: 99%
“…There is extensive evidence that β-carotene can produce major changes in immune cellular marker expression in vivo in humans (Prabhala, 1991), and has in fact been studied as a chemopreventive agent in the treatment of several precancerous lesions like oral leukoplakia, cervical dysplasia, breast carcinoma and esophageal adenocarcinoma (Cameron, 1995;Katz, 1998;Terry, 2000;Mayne, 2001;Bosetti, 2004;Nkondjock, 2004;SolaymaniDodaran, 2004). Regression of oral leukoplakia and gastric dysplasia with β-carotene therapy has been demonstrated in several clinical trials (Stich, 1988;Sankaranarayanan, 1997;Garewal, 1999;Correa, 2000). In addition, several animal studies have demonstrated evidence for inhibition of hepatic and pancreatic carcinogenesis by β-carotene therapy (Tsuda, 1994;Sarkar, 1995;Appel, 1996;Dagli, 1998;Majima, 1998).…”
Section: Barrett's Esophagus and β-Carotene Therapy: Symptomatic Imprmentioning
confidence: 99%